2020
DOI: 10.3390/rs12132079
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Sentinel-3A/3B and Jason-3 Altimeter Wind Speeds and Significant Wave Heights Using Buoy and ASCAT Data

Abstract: This study validated wind speed (WS) and significant wave height (SWH) retrievals from the Sentinel-3A/3B and Jason-3 altimeters for the period of data beginning 31 October 2019 (to 18 September 2019 for Jason-3) using moored buoy data and satellite Meteorological Operational Satellite Program (MetOp-A/B) Advanced Scatterometer (ASCAT) data. The spatial and temporal scales of the collocated data were 25 km and 30 min, respectively. The statistical metrics of root mean square error (RMSE), bias, correlation coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…It thus brings the model error and the subsequent bias for the retrieved wind speed. The bias at low winds also appears in wind retrievals from other sensors such as altimeter, SAR, and TRMM PR (Monaldo et al., 2016; Ren et al., 2016; Yang et al., 2020). For this problem, if the approximate wind speed range is known in advance, the bias may be corrected using a separated low wind model.…”
Section: Discussionmentioning
confidence: 88%
“…It thus brings the model error and the subsequent bias for the retrieved wind speed. The bias at low winds also appears in wind retrievals from other sensors such as altimeter, SAR, and TRMM PR (Monaldo et al., 2016; Ren et al., 2016; Yang et al., 2020). For this problem, if the approximate wind speed range is known in advance, the bias may be corrected using a separated low wind model.…”
Section: Discussionmentioning
confidence: 88%
“…Starting with Sentinel-3 performance, the results show that the accuracy of WS and SWH data derived by the Sentinel-3 satisfy their mission requirements. It is found that the accuracy of WS derived from Sentinel-3A/3B is better than that retrieved by Jason-3, while SWH accuracy derived from Jason-3 is better than the one from Sentinel-3A/3B [46]. Sentinel-3A SRAL data quality has been assessed by verifying data availability and monitoring the parameters of altimeter and radiometer through the global statistical analyses of Sentinel-3A Non-Time-Critical (NTC) Marine Level 2 products, in comparison with self-crossovers and cross-calibration with the Jason-3 mission, and the systemic bias of SSH about 2.96 cm shows consistency of the observation between Sentinel-3A SRAL and Jason-3, noting that Sentinel-3A SRAL has good and stable data quality [47].…”
Section: Resultsmentioning
confidence: 81%
“…The Pierson-Moskowitz (solid black) line indicates that the majority of the data is in developing seas closely associated with rain. Yang et al (2020) suggested that the accuracy of U 10 reduced when the H S measurement exceeds 4 meters, yet more than half of the data are populated in this state (H S > 5 m). In spite of the H S,Ku depicts many outliers for measurements above 5 m, the H S,C is more consistent with * 10 U even in wet conditions (above the average of W L ).…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…Matching criteria with spatial distance of less than 0.25° from the MetOps center pixel to the Jasons point and the temporal difference less than 30 min were applied. Similar criteria were applied by Yang et al (2020) when they validated Jason-3 to MetOps U 10 in normal conditions. This study only accepts the closest MetOps U 10 pixel to the Jasons point to preserve the highly dynamic variation that exists inside the tropical cyclone.…”
Section: Data Preparation and Spatio-temporal Match-upmentioning
confidence: 99%